Test Design and Evaluation for the Interim Armored Vehicle: Letter Report - National Research Council (The National Academies Press, 2002)

Letter Report on Scientific Assessment of the Redesigned Space Interferometry - National Research Council (The National Academies Press, 2002)

Summary: Assessment of Technologies Deployed to Improve Aviation Security: Second Report: Progress Toward Objectives - National Research Council (The National Academies Press, 2002)
This series of reports looks at technologies deployed by the FAA to improve aviation security. The first report recommends a system-of-systems approach for passenger and cargo screening combined with aircraft protection schemes, and suggests metrics to measure efficacy. The second report analyzes progress toward these goals.
Keywords: Engineering and Technology

The Impact of Acquisition Reform on Department of Defense Specifications and Standards for Materials and Processes: Report of the Workshop on Technical Strategies for Adoption of Commercial Materials and Processing Standards in Defense Procurement - National Research Council (The National Academies Press, 2002)
At the request of the U.S. Department of Defense (DoD), through its Defense Science and Technology Reliance Group Sub-area for Materials and Processes, a committee was formed by the National Materials Advisory Board to organize and conduct a workshop on technical strategies for the adoption of commercial standards in defense procurement. This book details the findings of that committee.
Keywords: Engineering and Technology

Update on the Engineering Design Studies Evaluated in the NRC Report, 'Analysis of Engineering Design Studies for Demilitarization of Assembled Chemical Weapons at Blue Grass Army Depot': Letter Report - National Research Council (The National Academies Press, 2002)

Reliability Issues for DOD Systems: Report of a Workshop - National Research Council (The National Academies Press, 2002)
The final report of the National Research Council's (NRC) Panel on Statistical Methods for Testing and Evaluating Defense Systems (National Research Council, 1998) was intended to provide broad advice to the U.S. Department of Defense (DoD) on current statistical methods and principles that could be applied to the developmental and operational testing and evaluation of defense systems. To that end, the report contained chapters on the use of testing as a tool of system development; current methods of experimental design; evaluation methods; methods for testing and assessing reliability, availability, and maintainability; software development and testing; and validation of modeling and simulation for use in operational test and evaluation. While the examination of such a wide variety of topics was useful in helping DoD understand the breadth of problems for which statistical methods could be applied and providing direction as to how the methods currently used could be improved, there was, quite naturally, a lack of detail in each area.To address the need for further detail, two DoD agencies-the Office of the Director of Operational Test and Evaluation and the Office of the Under Secretary of Defense for Acquisition, Technology, and Logistics-asked the NRC's Committee on National Statistics to initiate a series of workshops on statistical issues relevant to defense acquisition. The aim of each workshop is to inform DoD about the methods that represent the statistical state of the art and, through interactions of the statistical and defense communities, explore their relevance for DoD application.
Keywords: Conflict and Security Issues; Behavioral and Social Sciences; Surveys and Statistics

Privatization of Water Services in the United States: An Assessment of Issues and Experience - National Research Council (The National Academies Press, 2002)
In the quest to reduce costs and improve the efficiency of water and wastewater services, many communities in the United States are exploring the potential advantages of privatization of those services. Unlike other utility services, local governments have generally assumed responsibility for providing water services. Privatization of such services can include the outright sale of system assets, or various forms of public-private partnerships—from the simple provision of supplies and services, to private design construction and operation of treatment plants and distribution systems. Many factors are contributing to the growing interest in the privatization of water services. Higher operating costs, more stringent federal water quality and waste effluent standards, greater customer demands for quality and reliability, and an aging water delivery and wastewater collection and treatment infrastructure are all challenging municipalities that may be short of funds or technical capabilities. For municipalities with limited capacities to meet these challenges, privatization can be a viable alternative. Privatization of Water Services evaluates the fiscal and policy implications of privatization, scenarios in which privatization works best, and the efficiencies that may be gained by contracting with private water utilities.
Keywords: Earth Sciences

e-Transit: Electronic Business Strategies for Public Transportation, Volume 1, Supply Chain: Parts and Inventory Management - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2002)
TRB's Transit Cooperative Research Program (TCRP) Report 84: e-Transit: Electronic Business Strategies for Public Transportation, Volume 1, Supply Chain: Parts and Inventory Management examines the supply-chain concept and identifies supply-chain strategies used by nontransit fleets to reduce investments in parts and inventory while increasing fleet availability.
Keywords: Transportation and Infrastructure

Technology Development for Army Unmanned Ground Vehicles - National Research Council (The National Academies Press, 2002)
Unmanned ground vehicles (UGV) are expected to play a key role in the Army’s Objective Force structure. These UGVs would be used for weapons platforms, logistics carriers, and reconnaissance, surveillance, and target acquisition among other things. To examine aspects of the Army’s UGV program, assess technology readiness, and identify key issues in implementing UGV systems, among other questions, the Deputy Assistant Secretary of the Army for Research and Technology asked the National Research Council (NRC) to conduct a study of UGV technologies. This report discusses UGV operational requirements, current development efforts, and technology integration and roadmaps to the future. Key recommendations are presented addressing technical content, time lines, and milestones for the UGV efforts.
Keywords: Engineering and Technology; Conflict and Security Issues

An Assessment of Precision Time and Time Interval Science and Technology - National Research Council (The National Academies Press, 2002)
Knowledge of time is essential to precise knowledge of location, and for this reason the Navy, with its need to navigate on the high seas, has historically played an important role in the development and application of advanced time realization and dissemination technologies. Discoveries coming from basic research funded by the Office of Naval Research (ONR) lie at the heart of today's highest performance atomic clocks, Naval Research Laboratory (NRL) expertise played a role in developing the space-qualified atomic clocks that enable the Global Positioning System (GPS), and the U.S. Naval Observatory (USNO) maintains and disseminates the standard of time for all of the Department of Defense (DOD). The Navy has made major investments in most aspects of precision time and time interval (PTTI) science and technology, although specific PTTI-related research has also been funded by the Defense Advanced Research Projects Agency (DARPA) and non-DOD agencies such as the National Science Foundation (NSF), the National Aeronautics and Space Administration (NASA), and the Department of Commerce. Navy funding, largely through ONR, has a history of being an early enabler of key new developments. Judicious funding decisions by the Navy—particularly by ONR program officers—have underpinned most of the major advances in PTTI science and technology (S&T) in the last 50 years. PTTI is important to modern naval needs, and indeed to all the armed Services, for use in both navigation and communications. Precise time synchronization is needed to efficiently determine the start of a code sequence in secure communications, to perform navigation, and to locate the position of signal emitters. Precise frequency control is required in communications for spectrum utilization and frequency-hopped spread-spectrum techniques. There are many examples of essential military operations that depend on PTTI and could benefit from improvements in PTTI technology. These include: -GPS clocks and autonomous operations, -Weapon system four-dimensional coordination, -GPS antijamming, -Network-centric warfare, and -Secure military communications. This report summarizes that reductions in the size, weight, and power requirements and increases in the ruggedness of PTTI devices without sacrificing performance would put more accurate and precise timekeeping in the hands of the warrior, improving capabilities in all of the above operations.
Keywords: Math, Chemistry, and Physics; Space and Aeronautics

Combat Hybrid Power System Component Technologies: Technical Challenges and Research Priorities - National Research Council (The National Academies Press, 2002)
This book provides the detail from the NRC Committee on Assessment of Combat Hybrid Power Systems. This committee targeted three emerging technology areas: advanced electric motor drives and power electronics, battery technologies for military electric and hybrid vehicle applications, and high temperature wideband gap materials for high-power electrical systems. This committee also addressed three additional emerging technologies: high power switching technologies, capacitor technologies and computer simulation for storage system design and integration.
Keywords: Engineering and Technology

Broadband: Bringing Home the Bits - National Research Council (The National Academies Press, 2002)
Broadband communication expands our opportunities for entertainment, e-commerce and work at home, health care, education, and even e-government. It can make the Internet more useful to more people. But it all hinges on higher capacity in the "first mile" or "last mile" that connects the user to the larger communications network. That connection is often adequate for large organizations such as universities or corporations, but enhanced connections to homes are needed to reap the full social and economic promise. Broadband: Bringing Home the Bits provides a contemporary snapshot of technologies, strategies, and policies for improving our communications and information infrastructure. It explores the potential benefits of broadband, existing and projected demand, progress and failures in deployment, competition in the broadband industry, and costs and who pays them. Explanations of broadband's alphabet soup – HFC, DSL, FTTH, and all the rest – are included as well. The report's finding and recommendations address regulation, the roles of communities, needed research, and other aspects, including implications for the Telecommunications Act of 1996.
Keywords: Computers and Information Technology

High-Energy, Nutrient-Dense Emergency Relief Food Product - Institute of Medicine (The National Academies Press, 2002)
The present study was conducted by an ad hoc subcommittee of the Committee on Military Nutrition Research. The Subcommittee on Technical Specifications for a High-Energy Emergency Relief Ration was established by the Food and Nutrition Board of the Institute of Medicine in response to a request from USAID and DOD to develop technical specifications for a product for use in food relief after natural disasters or other emergency situations around the world. The specifications are to be used by both agencies in their calls for bids from U.S. food manufacturers to supply such a product.
Keywords: Food and Nutrition

Transfer of Pollution Prevention Technologies - National Research Council (The National Academies Press, 2002)
The activities of the Department of Defense (DOD) and its contractors in manufacturing, testing, maintaining, and disposing of military equipment make up a significant portion of the industrial processes conducted in the United States. As is the case with the commercial industries, some of these activities, such as metal plating, have resulted in industrial pollution and environmental contamination. With increasing environmental regulation of such processes in recent decades, defense facilities have been faced with growing compliance issues. Department of Defense efforts to manage, correct, and prevent these problems have included the establishment of the National Defense Center for Environmental Excellence (NDCEE) under the management of the U.S. Army Industrial Ecology Center (IEC).The National Research Council's Committee to Evaluate Transfer of Pollution Prevention Technology for the U.S. Army was formed to identify major barriers to the transfer of pollution prevention technologies and to recommend pathways to success. To address the study objectives, the committee (1) reviewed the NDCEE's technology transfer activities, (2) examined efforts to transfer technology in four areas, two of which were identified at the outset by the NDCEE as successful and two of which were identified as unsuccessful, and (3) identified opportunities for improving the transfer of pollution prevention technologies to maintenance and rework facilities in the Department of Defense and to industrial manufacturing facilities performing defense-related operations.
Keywords: Engineering and Technology

Implications of Emerging Micro- and Nanotechnologies - National Research Council (The National Academies Press, 2002)
Expansion of micro-technology applications and rapid advances in nano-science have generated considerable interest by the Air Force in how these developments will affect the nature of warfare and how it could exploit these trends. The report notes four principal themes emerging from the current technological trends: increased information capability, miniaturization, new materials, and increased functionality. Recommendations about Air Force roles in micro- and nanotechnology research are presented including those areas in which the Air Force should take the lead. The report also provides a number of technical and policy findings and recommendations that are critical for effective development of the Air Force’s micro- and nano-science and technology program
Keywords: Engineering and Technology

Regulation of Weights, Lengths, and Widths of Commercial Motor Vehicles: Special Report 267 - Transportation Research Board (The National Academies Press, 2002)
TRB Special Report 267 - Regulation of Weights, Lengths, and Widths of Commercial Motor Vehicles recommends the creation of an independent public organization to evaluate the effects of truck traffic, pilot studies of new truck designs, and a change in federal law authorizing states to issue permits for operation of larger trucks on the Interstates. In 1991, Congress placed a freeze on maximum truck weights and dimensions. Some safety groups were protesting against the safety implications of increased truck size and weight, and the railroads were objecting to the introduction of vehicles they deemed to have an unfair advantage. Railroads, unlike trucking firms, must pay for the capital costs of their infrastructure. The railroads contend that large trucks do not pay sufficient taxes to compensate for the highway damage they cause and the environmental costs they generate. Although Congress apparently hoped it had placed a cap on maximum truck dimensions in 1991, such has not proven to be the case. Carriers operating under specific conditions have been able to seek and obtain special exceptions from the federal freeze by appealing directly to Congress (without any formal review of the possible consequences), thereby encouraging additional firms to seek similar exceptions. In the Transportation Equity Act for the 21st Century, Congress requested a TRB study to review federal policies on commercial vehicle dimensions. The committee that undertook the study that resulted in Special Report 267 found that regulatory analyses of the benefits and costs of changes in truck dimensions are hampered by a lack of information. Regulatory decisions on such matters will always entail a degree of risk and uncertainty, but the degree of uncertainty surrounding truck issues is uunusually high and unnecessary. The committee concluded that the uncertainty could be alleviated if procedures were established for carrying out a program oof basic and applied research, and if evaluation and monitoring were permanent components of the administration of trucking regulations. The committee recommended immediate changes in federal regulations that would allow for a federally supervised permit program. The program would permit the operation of vehicles heavier than would normally be allowed, provided that the changes applied only to vehicles with a maximum weight of 90,000 pounds, double trailer configurations with each trailer up to 33 feet, and an overall weight limit governed by the federal bridge formula. Moreover, enforcement of trucks operating under such a program should be strengthened, and the permits should require that users pay the costs they occasion. States should be free to choose whether to participate in the permit program. Those that elected to do so would be required to have in place a program of bridge management, safety monitoring, enforcement, and cost recovery, overseen by the federal government. The fundamental problem involved in evaluating proposals for changes in truck dimensions is that their effects can often only be estimated or modeled. The data available for estimating safety consequences in particular are inadequate and probably always will be. Thus, the committee that conducted this study concluded that the resulting analyses usually involve a high degree of uncertainty. What is needed is some way to evaluate potential changes through limited and carefully controlled trials, much as proposed new drugs are tested before being allowed in widespread use. The committee recommended that a new independent entity be created to work with private industry in evaluating new concepts and recommending changes to regulatory agencies. Limited pilot tests would be required, which would need to be carefully designed to avoid undue risks and ensure proper evaluation. Special vehicles could be allowed to operate under carefully controlled circumstances, just as oversize and overweight vehicles are allowed to operate under special permits in many states. Changes in federal laws and regulations would be required to allow states to issue such permits on an expanded network of highways, under the condition that a rigorous program of monitoring and evaluation be instituted.Special Report 269 Summary
Keywords: Transportation and Infrastructure

Analysis of Engineering Design Studies for Demilitarization of Assembled Chemical Weapons at Blue Grass Army Depot - National Research Council (The National Academies Press, 2002)
Keywords: Environment and Environmental Studies; Math, Chemistry, and Physics

Characterization of Remote-Handled Transuranic Waste for the Waste Isolation Pilot Plant: Final Report - National Research Council (The National Academies Press, 2002)
The U.S. Department of Energy (DOE) disposes of plutonium-contaminated debris from its 27 nuclear weapons facilities at the Waste Isolation Pilot Plant (WIPP), an underground repository in Carlsbad, New Mexico. After four years of operational experience, DOE has opportunities to make changes to the costly and time-consuming process of "characterizing" the waste to confirm that it is appropriate for shipment to and disposal at WIPP.  The report says that in order to make such changes, DOE should conduct and publish a systematic and quantitative assessment to show that the proposed changes would not affect the protection of workers, the public, or the environment.
Keywords: Environment and Environmental Studies

Review of NASA's Earth Science Enterprise Applications Program Plan (The National Academies Press, 2002)
Keywords: Space and Aeronautics; Earth Sciences

Equipping Tomorrow's Military Force: Integration of Commercial and Military Manufacturing in 2010 and Beyond - National Research Council (The National Academies Press, 2002)
Owing to the expected nature of combat in 2010, U.S. military forces face a pressing need to transform themselves for rapid response to an unpredictable threat. Rapid advances in commercial technology (particularly in electronics), coupled with the easy access to commercial technology enjoyed by potential adversaries, will compel DOD and defense contractors to excel at integrating commercial technology into defense systems. This integration of commercial and military manufacturing (ICMM) has begun on a small scale. By 2010, it needs to increase substantially if U.S. forces are to retain a technological edge. This report assesses the opportunities for increased ICMM in 2010 and beyond, identifies barriers, and recommends strategies for overcoming them.
Keywords: Conflict and Security Issues; Engineering and Technology